Impact of temperature on survival, development and longevity of Aedes aegypti and Aedes albopictus (Diptera: Culicidae) in Phnom Penh, Cambodia - Bros Doeurk (Parasites & Vectors, 2025)
Abstract Background Aedes aegypti and Ae. albopictus are primary vectors of dengue virus in Cambodia, distributed throughout the country. Climate change is predicted to affect the relative density of these two species, but there is a lack of studies evaluating the impact of temperature on populations of these two species in this region. This study investigates the impact of temperature on the survival, development and longevity of Ae. aegypti and Ae. albopictus from populations collected in Phnom Penh, Cambodia. Methods Aedes aegypti and Ae. albopictus populations were collected in Phnom Penh. The experiment was conducted in a climatic chamber with temperatures ranging from 15 °C to 40 °C, with a 5 °C increment between each treatment. Bionomic parameters from the F2 egg hatching rate to the number of F3 eggs produced at each temperature treatment were measured. Results Temperature significantly influenced all life history traits of Ae. aegypti and Ae. albopictus. The highest egg hatching rates were observed at 25 °C for Ae. aegypti (97.97%) and 20 °C for Ae. albopictus (90.63%). Larvae of both species could not survive beyond the first stage at 40 °C. During immature stages, development time decreased at higher temperature (35 °C), but mortality was increased. Female longevity peaked at 25 °C for Ae. aegypti (66.7 days) and at 20 °C for Ae. albopictus (22.6 days), with males having significantly shorter lifespans. In addition, the optimal temperature for female survival is predicted higher in Ae. aegypti than in Ae. albopictus, at 27.1 °C and 24.5 °C, respectively. Wing length increased at lower temperatures, with Ae. aegypti consistently longer than Ae. albopictus at 15 °C and 35 °C. Blood-feeding rates were highest at 30 °C for Ae. aegypti (61.0%) and at 25 °C for Ae. albopictus (52.5%). Conclusion Aedes albopictus appears better adapted to lower temperatures, whereas Ae. aegypti is better adapted to higher temperatures. Warmer temperatures accelerate mosquito development but also increased mortality and reduced adult longevity, which could influence their ability to transmit pathogens. These findings highlight the critical role of temperature in mosquito biology and emphasize the potential impact of climate change on dengue transmission dynamics in the future. Graphical Abstract